INDUCTIVE RISK AND JUSTICE IN KIDNEY ALLOCATION - Scarantino, Andrea (Bioethics, 2010)
How should UNOS deal with the presence of scientific controversies on the risk factors for organ rejection when designing its allocation policies? The answer I defend in this paper is that the more undesirable the consequences of making a mistake in accepting a scientific hypothesis, the higher the degree of confirmation required for its acceptance. I argue that the application of this principle should lead to the rejection of the hypothesis that ‘less than perfect’ Human Leucocyte Antigen (HLA) matches are an important determinant of kidney graft survival. The scientific community has been divided all along on the significance of partial antigen matches. Yet reliance on partial matches has emerged as one of the primary factors leading blacks to spend a much longer time than whites on the waiting list for kidneys, thereby potentially impacting the justice of the kidney allocation policy. My case study illustrates one of the legitimate roles non-epistemic values can play in science and calls into question the ideal of a value-free science.